Static Langer's line and wound contraction rates according to anatomical regions in a porcine model. Issue 5 (September 2014) - Kwak, Minho; Son, Daegu; Kim, Junhyung; Han, Kihwan
Abstract This study investigated wound contraction rates according to anatomical regions and wound morphology according to skin tension line in a micropig porcine model. Of the four animals used, skin tension morphology was determined in one pig. In the remaining three pigs, six pairs of full‐thickness skin excisions were created on the dorsum (six square and six circular). The wounds were grouped, Wounds #1 through #5, according to the skin tension line and anatomical regions: Wounds #1 and #2, cephalic; Wounds #4 and #5, caudal; and Wound #3, center. Wound sizes and contraction rates were calculated for 28 days. A static tension topography of the micropig dorsum was obtained. Excisional wounds deformed along the local tension vector and healed in this fashion. Wound contraction rates were significantly higher for cephalic wounds (p = 0.004). No significant difference in wound contraction rates were observed between square and circular wounds. Final wound morphology was related to the local tension vector and initial wound shape. Cephalic wounds contracted more quickly. Further studies are needed to characterize scar formation after primarily closed surgical wounds in relation to the newly established skin tension topography and to elucidate the mechanism behind the variable wound contraction rates in the cephalocaudal gradient.